Brief Study of Metal-substituted ZSM-5 -Potential Application in Methanol Production (Nusantara Science and Technology Proceedings, 2021)
This article clarifies the potential of Zeolite Socony Mobil-5 (ZSM-5) substituted metals such as Copper (II) (Cu) and Iron (III) (Fe) as a catalyst in the methane oxidation reaction to methanol. The authors described the physical and chemical characteristics of modified ZSM-5 with Cu and Fe as well as the fundamental theory in predicting the reaction mechanism and performance of the catalyst active site which is crucial to producing methanol from methane. Methanol has a high economic value and supplies the essential raw materials in energy, petrochemical, pharmaceutical, and environmental industries. Therefore, it is very necessary to have this basic knowledge to increase the efficiency and effectiveness of catalyst performance and enhance the green production process. The reason behind the widely used modified ZSM-5, it was easily applied in the low and intermediates temperature range, and the structure was easy to modify according to the desired performance.